Sex differences in children and adolescents with attention-deficit/hyperactivity disorder: a literature review - Dimitri, Danilo; Delia, Giuliana; Cavallo, Francesco; Varini, Matteo; Fioretto, Franco (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionThis systematic review aimed to synthesize existing research on the symptomatological and behavioural differences between male and female attention-deficit/hyperactivity disorder (ADHD) in individuals aged 6–18 years. ADHD is a prevalent neurodevelopmental disorder that manifests differently across genders, potentially impacting the diagnosis, treatment, and overall management of the condition.MethodsFollowing the Preferred Reporting Items for Systematic reviews and Meta-Analyses 2020 (PRISMA guidelines), we conducted a comprehensive literature search and identified 67 records published between 2008 and 2024 that met our inclusion criteria. The review examined both direct sex differences—comparing female ADHD subjects to their male counterparts—and the disorder's sex-specific effects, revealing nuanced patterns of compromission.ResultsFindings were organized into seven thematic areas: core symptoms, executive and attention performance, neuropsychomotor aspects, psychopathological aspects, behavioural and social aspects, substance use and academic performance. Differences between males and females with ADHD have been highlighted across several domains, including prevalence and intensity of core symptoms, cognitive functioning, and the nature of externalizing vs internalizing behaviours. Notably, variations were observed in the ways symptoms manifest, such as in aggression and emotional regulation. Furthermore, the review highlighted how ADHD's impact is influenced by the subject's sex, specifically affecting neuropsychomotor development, social interactions, and self-esteem. Age-related differences concerning the evolution of symptoms and cognitive functions were also explored, shedding light on how developmental trajectories may differ between sexes. ConclusionA comprehensive understanding of sex specificity in relation to ADHD is critical for informing effective diagnosis and treatment strategies. This review underscores the need for further research to elucidate these differences, ultimately contributing to more tailored and sex-sensitive approaches in ADHD management.Systematic Review Registrationhttps://doi.org/10.37766/inplasy2025.4.0093, identifier INPLASY202540093.